Effect of Prior Bariatric Surgery on the Outcomes of Joint Arthroplasty: A Systematic Review and Meta-Analysis - Zhou Zhang; Xiang Shi; Wei Liu; Jianwei Wang; Qingfeng Shen; Guozhu Xu; Jiakuan Bao; Yupeng Dong (Journal of Investigative Surgery)
Objective Obesity is a risk factor for joint arthroplasty complications. With this systematic review and meta-analysis, we assessed whether a positive history of bariatric surgery influences postoperative outcomes in patients undergoing various types of joint arthroplasty.Methods We conducted a comprehensive search database such as Scopus, PubMed, Medline Ovid, CNKI, and CENTRAL for studies comparing outcomes between patients undergoing arthroplasty with and without a history of bariatric surgery. We extracted data on short-term medical complications, venous thromboembolism (VTE), periprosthetic infections, superficial wound infections, hospital stay length, and operative time. We used the data to conduct meta-analyses using random-effects models and subgroup analyses based on the type of arthroplasty.Results Overall, 15 studies with nearly 150,000 participants were included. The analysis showed that prior bariatric surgery did not significantly affect overall medical complications post-arthroplasty, with OR of 0.968 (95%CI, 0.706-1.327). For VTE, the results similarly indicated no substantial difference, with an OR of 0.912 (95%CI, 0.644-1.291). In assessing periprosthetic infections, the OR was 0.754 (95%CI, 0.535-1.064), showing comparable rates between patients with and without a history of bariatric surgery.Regarding superficial wound infections, the analysis produced an OR of 2.390 (95%CI, 0.723-7.897), indicating variability but not statistical significance. Hospital stay length was reduced in patients with a history of bariatric surgery, reflected by SMD of −0.113 (95%CI, −0.221 to −0.005). Lastly, operative time also showed a significant reduction, with an SMD of −0.462 (95%CI, −0.865 to −0.059).Conclusions Prior bariatric surgery does not reduce the risk of short-term complications post-arthroplasty, but it seems to reduce the hospital stay length and operative time. The effects vary significantly across different types of joint arthroplasty, suggesting a need for tailored preoperative assessments and care protocols.Protocol registration This systematic review and meta-analysis was registered at PROSPERO, with the number: CRD42024539052